COMPARATIVE EFFECT OF COUNTER STRAIN TECHNIQUE AND POST ISOMETRIC RELAXATION TECHNIQUE ON PAIN, FATIGUE AND FUNCTIONAL DISABILITY IN THORACIC MYOFASCIAL PAIN SYNDROME (Journal of Medical & Health Sciences Review, 2025)
Introduction: Thoracic Myofascial Pain Syndrome  is a localized musculoskeletal pain condition characterized by the presence of myofascial trigger points in the thoracic region. Conventional therapies are widely used for its management; however, this study aimed to compare the effectiveness of two manual therapy techniques: strain-counterstrain  and post-isometric relaxation.Materials and Methodology:  An experimental study was conducted on 30 patients diagnosed with thoracic myofascial pain syndrome using a convenient sampling technique. Participants were randomly assigned into two groups (n=15 each) using a computer-generated random number method. Group A received the strain counterstrain technique in combination with a hot pack and massage gun, while Group B received post-isometric relaxation technique along with a hot pack and massage gun. Outcome measures included the Visual Analogue Scale for pain, Modified Pain Disability Questionnaire for functional disability, and Fatigue Severity Scale for fatigue assessment. Data were analyzed using SPSS version 27.Conclusion: The study found that both interventions were effective in reducing pain, fatigue, and functional disability in patients with thoracic myofascial pain syndrome. However, the strain-counterstrain technique demonstrated significantly greater improvements across all outcome measures compared to the post-isometric relaxation technique. Thus, Strain counterstrain technique may be considered a more effective approach for the management of thoracic myofascial pain syndrome when used alongside standard modalities such as heat therapy and massage.